НӨКИС ҚАЛАСЫНЫҢ СОЦИАЛ-ЭКОНОМИКАЛЫҚ РАЎАЖЛАНЫЎЫНЫҢ ТИЙКАРЛАРЫ (1991-2014-жыллар) - Есназарова, З.Б.; Алеуов, З. (FAN va JAMIYAT, 2020)
The article is devoted to deep analysis of the state of the social-economic development of the Republic of Karakalpakstan on the example of the city Nukus at the early period of Independence in 1991-2014. As the main social-cultural and political-economic centre our capital has always been the important key-point of all successes in wellbeing of our people. Historically analizing the situation the author points to the objective and subjective factors which accompanied industrial enterprizes, establishments and organizations of the city of Nukus in their beneficial duties of raising the social-economic level and well-being of the whole population of the capital, confirming the facts by official documents with a great historical importance. The author of the article deseribed the important issues of administrative bodies and farning subjects in the realization of economical reform that help to overcome the difficulties of the period.